2014
DOI: 10.1111/ctr.12412
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial complications in adult living donor liver transplant recipients: a single‐center experience of 673 cases

Abstract: Because hepatic arterial complications after LDLT are associated with poor patient survival, early diagnosis and immediate treatment are crucial. The anatomical anastomosis may be the first choice for the hepatic arterial reconstruction to the extent possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…57,65,66 Other studies have demonstrated that extra-anatomic anastomosis was the only multivariate factor independently associated with hepatic artery complications in the living donor transplant recipient. 67 HAT in the transplantation literature usually is discovered on serial Doppler ultrasounds, which are an integral component of postoperative care for the patient after transplantation; however, computed tomography (CT) scans also may provide information on HAT. As there are no large series of hepatic artery resection in liver resection, it is difficult to definitively identify relevant risk factors in this population of patients.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…57,65,66 Other studies have demonstrated that extra-anatomic anastomosis was the only multivariate factor independently associated with hepatic artery complications in the living donor transplant recipient. 67 HAT in the transplantation literature usually is discovered on serial Doppler ultrasounds, which are an integral component of postoperative care for the patient after transplantation; however, computed tomography (CT) scans also may provide information on HAT. As there are no large series of hepatic artery resection in liver resection, it is difficult to definitively identify relevant risk factors in this population of patients.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Interventional radiology-based procedures, such as angioplasty, can be considered; however, urgent surgical thrombectomy may be required to reestablish flow. 67 PVT can be managed in various ways, as reviewed by Thomas and Ahmad 68 in 2010. Anticoagulation with intravenous heparin followed by long-term warfarin has reduced the risk of thrombotic events and promoted the recanalization of the vein.…”
Section: Managementmentioning
confidence: 99%
“…Hepatic artery thrombosis (HAT) is an uncommon complication after liver transplantation with serious clinical implications including graft loss and increased recipient mortality . Surgical risk factors including organ cold ischemia time (CIT), surgical technique, delay in reperfusion, and anatomic abnormalities all likely play a role in outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…The hepatic arteries that are reconstructed in LDLT are usually thinner in diameter and have a shorter stalk than those in deceased‐donor liver transplantation—especially when left hepatic grafts are used. Many surgeons prefer to reconstruct hepatic arteries in LDLT using a microvascular surgical technique . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The recently reported incidence of hepatic artery-related complication at high volume centers for AALDLT ranged from 1.6% to 6.5%. 5,[13][14][15][16][17] The hepatic arteries that are reconstructed in LDLT are usually thinner in diameter and have a shorter stalk than those in deceased-donor liver transplantation-especially when left hepatic grafts are used. Many surgeons prefer to reconstruct hepatic arteries in LDLT using a microvascular surgical technique.…”
Section: Discussionmentioning
confidence: 99%